Penguatan Pemahaman Awal Guru tentang Pendekatan Deep Learning - Manalu, Andriono; Silaban, Winarto; Rajagukguk, Tommi Perkasa; Purba, Ika Damayanti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Deep Learning method aims to create a learning experience that is not only deeper, but also enjoyable and meaningful for students. Instead of simply memorizing facts, students are encouraged to think critically, reflect on what they learn, and connect new knowledge to their daily lives. This approach highlights three important aspects: Mindful Learning, which helps students become more aware and intentional in their learning; Meaningful Learning, which ensures that lessons are relevant and have a real impact; and Joyful Learning, which brings a sense of happiness and enthusiasm into the classroom. In this community service program, the authors set out to introduce and strengthen teachers’ understanding of Deep Learning. The activities included sharing theories, discussing practical examples from different regions, and inviting teachers to reflect on their own experiences. The program was held at Huta Bayu Private High School in Simalungun Regency. Based on the initial observations, many teachers felt that Deep Learning is not very different from the independent curriculum, or Kurikulum Merdeka, that has already been put into practice at their school. This shows that while the term may sound new, the main ideas behind Deep Learning are already familiar and have begun to take root in everyday teaching.